Charter schools : lessons in school reform - Brouillette, Liane, 1947- (Topics in educational leadership., 2002)
"Charter Schools: Lessons in School Reform investigates the strengths and limitations of charter schools as an approach to reform by focusing on the day-to-day reality of students, teachers, administrators, and parents involved. Detailed case studies of seven schools, in three states are included. Seymour Sarason's work on the creation of settings provides the lens through which these schools are examined. The book takes the reader inside the charter school movement, answering such questions as: what is a charter school?; how do charter schools differ from other public schools?; what does it take to create a charter school?; what motivates the people who initiate such schools?; what lessons can be learned from the experiences of those who have founded charter schools?; and what does the growth of the charter school movement mean for society at large?" "Charter Schools Lessons in School Reform is important reading for anyone interested in charter schools, particularly individuals who are contemplating the establishment of charter schools, school practitioners, and professors and students in teacher or administrator preparation programs."--Jacket